Kekuatan Eksekutorial Sertifikat Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Kintannia Khairunnissa Indriyanti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
A fiduciary guarantee agreement is a formal agreement that must be stated in a notarial deed as regulated in Article 4 of the Fiduciary Guarantee Law. This provision states that a fiduciary guarantee is a subsidiary agreement of the main agreement that creates an obligation for the parties to fulfill a performance. Execution, in this context, is a legal action carried out based on a legally binding decision. Article 15 paragraph (2) of the Fiduciary Law explains that the executorial power of a fiduciary guarantee certificate allows for direct implementation without going through a court, is final, and binds the parties. This research uses an empirical normative method, namely combining library studies with field research. Primary data was obtained through interviews with Judges of the Yogyakarta District Court, Judges of the Sleman District Court, the Yogyakarta State Assets and Auction Service Office (KPKNL), and the Yogyakarta Regional Office of the Ministry of Law and Human Rights. Secondary data comes from primary, secondary, and tertiary legal materials. The analysis was conducted qualitatively. The research results indicate that following Constitutional Court Decision No. 18/PUU-XVII/2019, the execution of fiduciary collateral objects can no longer be carried out unilaterally by creditors, but must instead be filed through the District Court. This provision balances the legal standing between debtors and creditors and prevents potential arbitrariness. Nevertheless, execution through the courts is an alternative if there is no agreement between the parties regarding a default. The court's role following the Constitutional Court decision includes resolving disputes between creditors and debtors and ensuring that execution procedures are carried out in accordance with the HIR (Regional Regulations for the Protection of Creditors), RBG (Regional Regulations for the Protection of Creditors), and the Supreme Court's technical instructions. In general, the execution mechanism through the courts is considered quite effective in ensuring legal protection for both parties.